Analytical Strategies and Musical Interpretation: Essays on Nineteenth-and Twentieth-Century Music - Ayrey, Craig; Everist, Mark (Cambridge Cambridge University Press, 1996)
This book is devoted to music analysis as an interpretive activity. Interpretation is often considered only in theory, or as a philosophical problem, but this book attempts to demonstrate and reflect on the interpretive results of analysis. Two associated types of practice are emphasised: 'translation', the transformation of one type of experience or art object into the musical work, the artistic attempt to persuade us that the new product is as valid as its original, or more so than its origin; and 'rhetoric', the attempt to persuade us, through structure, to accept the signifying power of the work. The unifying theme of the essays is the interpretive transformation of concepts, ideas and forms that constitutes the heart of the compositional process of nineteenth- and twentieth-century music. The repertoire discussed ranges from Schumann through Wagner, Mahler, Zemlinsky, Debussy, Schoenberg, Berg, Webern and Stravinsky to Carter and Birtwistle.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Musical analysis; Musical interpretation